Ninth Five Year Plan 1997-2002 Draft Prepared at the Internal Meetings of the Planning Commission Volume I - Planning Commission, Government of India (Planning Commission, Government of India, 1997)
The Ninth Five-Year Plan is being launched in the 50th year of India’s Independence. Much has happened in the intervening years. The people of India have conclusively demonstrated their ability to build up a nation overcoming all the divisiveness and to operate a representative political system in the true spirit of democracy. The time has now come to extend this spirit to the social and economic spheres in full measure, so that the poorest and the weakest will be able to shape their destiny in an unfettered manner. This will require not only higher rates of growth of output and employment, but an all-round human development with stress on social sectors and a thrust on eradication ®f poverty, minimizing economic disparities and correcting regional imbalances.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Ninth Five Year Plan- India; Economic development